Cloning, Expression and Purification of an Acetoacetyl CoA Thiolase from Sunflower Cotyledon - Dyer, James H. (Ivyspring International Publisher, 2009)
Thiolase I and II coexist as part of the glyoxysomal β-oxidation system in sunflower (Helianthus annuus L.) cotyledons, the only system shown to have both forms. The importance of thiolases can be underscored not only by their ubiquity, but also by their involvement in a wide variety of processes in plants, animals and bacteria. Here we describe the cloning, expression and purification of acetoacetyl CoA thiolase (AACT) in enzymatically active form. Use of the extensive amount of sequence information from the databases facilitated the efficient generation of the gene-specific primers used in the RACE protocols. The recombinant AACT (1233 bp) shares 75% similarity with other plant AACTs. Comparison of specific activity of this recombinant AACT to a previously reported enzyme purified from primary sunflower cotyledon tissue was very similar (263 nkat/mg protein vs 220 nkat/mg protein, respectively). Combining the most pure fractions from the affinity column, the enzyme was purified 88-fold with a 55% yield of the enzymatically active, 47 kDa AACT.